Development of a nanodroplet formulation for triggered release of BIO for bone fracture healing - May, JP; Polydorou, A; Ferri, S; Wu, Q; Stride, E; Carugo, D; Evans, ND (MDPI, 2020)
Impaired fracture healing impacts patients’ quality of life and imposes a financial burden on healthcare services. Up to 10% of bone fractures result in delayed/non-union fractures, for which new treatments are urgently required. However, systemic delivery of bone anabolic molecules is often sub-optimal and can lead to significant side effects. In this study, we developed ultrasound (US) responsive nano-sized vehicles in the form of perfluorocarbon nanodroplets (NDs), as a means of targeting delivery of drugs to localised tissues. We tested the hypothesis that NDs could stably encapsulate BIO (GSK-3β inhibitor), which could then be released upon US stimulation to activate Wnt signalling and induce ossification. NDs (~280 nm) were prepared from phospholipids and liquid perfluorocarbon and their stability and drug loading was studied by NTA (Nano Tracking Analysis) and HPLC. ND cytotoxicity was assessed in patient-derived bone marrow stromal cells (BMSCs) with Alamar Blue (24 h), and in vitro bioactivity of BIO-NDs was evaluated in a 3T3 Wnt-pathway reporter cell line with luciferase readout. To investigate the acoustic behaviour of NDs, 2% agarose (LM) containing NDs was injected into a bespoke bone fracture model (Sawbones) of various geometries and stimulated by US (1 MHz, 5% duty cycle, 1 MPa, 30 s), allowing the simultaneous capture of optical images and acoustic emissions. Femoral bone hole defects (1–2 mm) were made in WT-MF1 mice (age: 8–12 wks) and DiR-labelled NDs (100 µL, 109 NDs/mL, i.v.) were injected post-fracture to determine biodistribution by IVIS imaging. NDs were stable (4 and 37 °C) and retained >90% BIO until US was applied, which caused ~100% release. ND exposure up to a concentration of 109 NDs/mL showed no cytotoxicity (24 h). BIO-loaded NDs induced Wnt pathway activation in a dose dependent manner. Biodistribution of DiR-NDs in a femoral bone hole defect model in mice demonstrated increased localisation at the fracture site (~2-fold relative to that found in healthy mice or contralateral femurs at 48 h).